″Research competence of the educator under the conditions of the introduction of innovative teaching technologies″ - Bachiieva, L. (Problems of Engineer-Pedagogical Education, 2018)
The article presents the results of theoretical research on the definition of the concept of the pedagogue’s research competence in the context of the introduction of innovative teaching technologies. The analysis of the concept of "research competence" in the sequence from its understanding, definition and structure in the system of general, vocational, higher and postgraduate education is carried out. Its peculiarities are presented in the context of carrying out research basing on the results of the introduction of innovative teaching technologies. A component-structural analysis of the concept allowed the researcher to identify cognitive, operational-technological, activity-based, personal, reflexive, motivational and value-oriented components. The article presents characteristics of each of the above-named components, analyzes four groups of knowledge and skills that form the basis for the development of the pedagogue’s research competence under the conditions of introducing innovative teaching technologies, and defines the content of the groups of research knowledge and skills: informational and analytical, modeling and design, experimental and measuring, evaluative and reflexive. Research competence is proved to be a necessary quality of the educator as it provides the innovativeness of the pedagogue’s professional activity since innovations are the result of scientific researches, analysis, and generalization of former educational experience.